Flow-Diversion Effect of LEO Stents: Aneurysm Occlusion and Flow Remodeling of Covered Side Branches and Perforators - Cagnazzo, F.; Cappucci, M.; Dargazanli, C.; Lefevre, P.-H.; Gascou, G.; Riquelme, C.; Morganti, R.; Mazzotti, V.; Bonafe, A.; Costalat, V. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Flow diversion with intermediate-porosity stents (braided stents) has been recently reported for distally located small aneurysms. The aim of this study was to evaluate the flow-diversion effect of LEO stents on covered vessels and for aneurysms treated with sole stent-placement therapy.MATERIALS AND METHODS: We retrospectively evaluated the following outcomes: 1) remodeling of covered side branches and perforators (extra-aneurysmal flow remodeling), and 2) the occlusion rate of aneurysms treated with sole stent-placement therapy (intra-aneurysmal flow remodeling).RESULTS: Seventy-six patients with 98 covered vessels were studied. Overall, 89 covered arteries (91%) were normal, 7 showed narrowing (7%), and 2 (2%) were occluded (1 posterior communicating artery and 1 MCA) without related complications (mean DSA follow-up, 14 months). Univariate and multivariate analyses highlighted smoking (P = .03) and the length of follow-up (P = .002) as factors associated with arterial remodeling. Of the 17 Sylvian (lenticulostriate arteries) and 7 basilar perforators, 1 (4%) group of Sylvian perforators covered with double stents had asymptomatic remodeling. Ten aneurysms (mean size, 3.5 mm) were treated with LEO stents as stent monotherapy (5 recanalized after coiling and 5 directly treated with the LEO). Complete occlusion (Raymond-Roy I) was achieved in 70% of aneurysms (mean follow-up, 14 months). The Raymond-Roy I occlusion rate among recanalized aneurysms and those directly treated with LEO stents was 80% and 60%, respectively (P = .9).CONCLUSIONS: The rate of flow remodeling on the covered arteries and perforators was 9% and 4%, respectively, and was clinically irrelevant in all cases. Complete occlusion of aneurysms treated with sole stent-placement therapy was 70%. These data stress the flow-diversion properties of LEO stents.PcomAposterior communicating arteryRRRaymond-RoySACstent-assisted coiling